Polarizing plate and display device using same
By sticking protective films A and B with specific moisture permeability and layer structure on the polarizer, the problem of deterioration of the polarizer caused by moisture entering in high temperature and high humidity environment is solved, and the high durability of the polarizer is achieved.
Patent Information
- Application Number
- CN202380063073.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-10-06
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-08
AI Technical Summary
In high temperature and high humidity environment, the protective film of the existing polarizer cannot effectively prevent moisture from entering, resulting in deterioration of water absorption of polyvinyl alcohol (PVA) substrate.
A polarizing plate design is adopted in which the protective film A is pasted on one side of the polarizing plate and the protective film B is pasted on the other side. Protective film A has a transparent substrate, a hard coating and a compatible layer, with a moisture permeability of between 70 g/m2/day and 240 g/m2/day; Protective film B has a moisture permeability of 70 g/m2/day or less. The thickness of the top layer meets a specific ratio with the thickness of the compatible layer to ensure that moisture does not enter and release at high temperatures.
It effectively suppresses moisture entering the polarizing plate, prevents water absorption and deterioration of the PVA substrate, and improves the durability of the polarizing plate in high temperature and high humidity environments.
Smart Images

Figure CN119790332A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polarizing plate and a display device using the polarizing plate. Background Art
[0002] Polyvinyl alcohol (PVA) is mainly used in polarizing plates used in display devices. PVA has extremely poor water resistance, so protective films are attached to both sides. In the past, protective films for polarizing plates used triacetyl cellulose (TAC) films laminated with a hard coating layer, with a moisture permeability of 300 to 1000 g / m 2 / day or so, but there is a problem that under the severe conditions of high temperature and high humidity, it is impossible to prevent PVA from absorbing water and causing degradation.
[0003] Therefore, protective films using cycloolefin polymer (COP) and polyethylene terephthalate (PET) instead of TAC have been developed, and the moisture permeability of the protective films can be reduced to 5 to 100 g / m 2 / day or so.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2021-144076 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In recent years, polarizing plates with durability under extremely high temperature and humidity have been required for automotive applications, etc. In high temperature and humidity environments, when the water vapor barrier property of the protective film is too high, although there is no moisture intrusion from the outside, there are cases where moisture generated from the substrate or the adhesive used to attach the protective film stays in the polarizing plate and causes deterioration.
[0009] Therefore, an object of the present invention is to provide a polarizing plate having durability in a high-temperature and high-humidity environment and a display device using the polarizing plate.
[0010] Means for solving problems
[0011] The polarizing plate involved in the present invention is a polarizing plate having a protective film A attached to one surface of a polarizer and a protective film B attached to the other surface, wherein the protective film A is a hard coating film having a hard coating layer formed on one surface of a transparent substrate, and comprises a substrate layer composed of a resin component of the transparent substrate, an outermost layer composed of a hard coating component, and a compatibility layer formed between the substrate layer and the outermost layer and containing a mixture of the resin component of the transparent substrate and the hard coating component, wherein the moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B at 40°C and 90%RH simultaneously satisfy the following conditions (1) and (2), and the thickness a of the outermost layer and the thickness b of the compatibility layer satisfy the following condition (3).
[0012] 240g / m 2 / day>TA>70g / m 2 / day…(1)
[0013] 70g / m 2 / day≥TB…(2)
[0014] 0.60≤a / b≤0.85…(3)
[0015] Furthermore, a display device according to the present invention includes the above-mentioned polarizing plate.
[0016] Effects of the Invention
[0017] According to the present invention, a polarizing plate having durability in a high-temperature and high-humidity environment and a display device using the polarizing plate can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] [ Figure 1 ] Figure 1 It is a cross-sectional view showing a schematic structure of a polarizing plate according to an embodiment.
[0019] [ Figure 2 ] Figure 2 It is shown Figure 1 A cross-sectional view showing a schematic structure of the protective film A shown. DETAILED DESCRIPTION
[0020] Figure 1 It is a cross-sectional view showing a schematic structure of a polarizing plate according to an embodiment.
[0021] The polarizing plate 10 includes a polarizer 1, a protective film A attached to one side of the polarizer 1, and a protective film B attached to the other side of the polarizer 1. The polarizer 1 is formed by adsorbing iodine or a dye on a polyvinyl alcohol (PVA) film and orienting it. Since the PVA constituting the polarizer 1 has poor strength and water resistance, the protective films A and B are attached to both sides of the polarizer 1.
[0022] The protective film A is a hard coating film having a hard coating layer formed on one surface of a transparent substrate. The hard coating layer is a functional layer that covers the soft transparent substrate and imparts hardness and water vapor barrier properties to the protective film A. As the transparent substrate, a triacetyl cellulose (TAC) film having excellent transparency can be preferably used.
[0023] Figure 2 It is shown Figure 1 A cross-sectional view showing a schematic structure of the protective film A shown.
[0024] The protective film A can be formed by applying a hard coat layer-forming composition containing an active energy ray-curable compound, a hydrophobic material, a photopolymerization initiator and a solvent on one surface of a transparent substrate, drying the composition and curing the coating by ultraviolet irradiation.
[0025] When the hard coat-forming composition is applied to a transparent substrate, a portion of the transparent substrate swells or dissolves due to the solvent contained in the hard coat-forming composition, forming a layer in which the components of the hard coat-forming composition (hard coat component) and the resin component constituting the transparent substrate are mixed. After the hard coat-forming composition is dried, when the coating is cured by ultraviolet irradiation, such as Figure 2 As shown, a substrate layer 2 with a resin component of a transparent substrate as the main body, a cured layer with a hard coating component as the main body, i.e., an outermost layer 3, and a compatible layer 4 formed between the substrate layer 2 and the outermost layer 3 and mixed with the resin component of the transparent substrate and the hard coating component and cured are formed. It should be noted that the interface between the substrate layer 2 and the compatible layer 4 and the interface between the compatible layer 4 and the outermost layer 3 can be confirmed by cross-sectional observation of the protective film A using a scanning electron microscope (SEM), and the thickness of the substrate layer 2, the compatible layer 4 and the outermost layer 3 can be determined by the SEM image. The thickness of the compatible layer 4 can be controlled by the drying time or drying temperature after applying the hard coating forming composition. For example, when the drying time is extended, the swelling or dissolution of the transparent substrate caused by the solvent is further carried out, so the compatible layer 4 can be made thicker. In addition, when the drying temperature is increased, the drying is carried out faster, so the swelling or dissolution of the transparent substrate caused by the solvent can be suppressed, thereby making the compatible layer 4 thinner.
[0026] As the active energy ray-curable compound, for example, a monofunctional, bifunctional, or trifunctional or higher (meth)acrylate monomer can be used. It should be noted that in this specification, "(meth)acrylate" is a general term for both acrylate and methacrylate, and "(meth)acryloyl" is a general term for both acryloyl and methacryloyl.
[0027] Examples of the monofunctional (meth)acrylate compound include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, glycidyl (meth)acrylate, acryloylmorpholine, N-vinylpyrrolidone, tetrahydrofurfuryl acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, isobornyl (meth)acrylate, and (meth)acrylate. Isodecyl acrylate, lauryl (meth)acrylate, tridecyl (meth)acrylate, hexadecyl (meth)acrylate, octadecyl (meth)acrylate, benzyl (meth)acrylate, 2-ethoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, ethyl carbitol (meth)acrylate, phosphoric acid (meth)acrylate, ethylene oxide modified phosphoric acid (meth)acrylate, phenoxy (meth)acrylate, ethylene oxide modified phenoxy (meth)acrylate, propylene oxide modified phenoxy (meth)acrylate meth)acrylate, phenol (meth)acrylate, ethylene oxide modified nonylphenol (meth)acrylate, propylene oxide modified nonylphenol (meth)acrylate, methoxydiethylene glycol (meth)acrylate, methoxypolyethylene glycol (meth)acrylate, methoxypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl hydrogenated phthalate, 2-(meth)acryloyloxyethyl hydrogenated phthalate -(meth)acryloxypropyl ester, 2-(meth)acryloxypropyl hexahydrohydrophthalate, 2-(meth)acryloxypropyl tetrahydrohydrophthalate, dimethylaminoethyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, hexafluoropropyl (meth)acrylate, octafluoropropyl (meth)acrylate, and adamantane derivative mono(meth)acrylate such as adamantane acrylate having a monovalent mono(meth)acrylate derived from 2-adamantane or adamantanediol.
[0028] Examples of the bifunctional (meth)acrylate include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, butanediol di(meth)acrylate, hexanediol di(meth)acrylate, nonanediol di(meth)acrylate, ethoxylated hexanediol di(meth)acrylate, propoxylated hexanediol di(meth)acrylate, diethylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, ethoxylated neopentyl glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, hydroxypivalate neopentyl glycol di(meth)acrylate and other di(meth)acrylates.
[0029] Examples of trifunctional or higher (meth)acrylates include trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane tri(meth)acrylate, propoxylated trimethylolpropane tri(meth)acrylate, tri-2-hydroxyethyl isocyanurate tri(meth)acrylate, glycerol tri(meth)acrylate and the like; trifunctional (meth)acrylates such as pentaerythritol tri(meth)acrylate, dipentaerythritol tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate and the like; Acid ester compounds; polyfunctional (meth)acrylate compounds having three or more functions such as pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, ditrimethylolpropane penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and ditrimethylolpropane hexa(meth)acrylate; and polyfunctional (meth)acrylate compounds in which a part of these (meth)acrylates is substituted with an alkyl group or ε-caprolactone, etc.
[0030] In addition, urethane (meth)acrylates may be used as the polyfunctional monomers. Examples of urethane (meth)acrylates include urethane (meth)acrylates obtained by reacting a product obtained by reacting an isocyanate monomer or prepolymer with a polyester polyol with a (meth)acrylate monomer having a hydroxyl group.
[0031] Examples of urethane (meth)acrylates include pentaerythritol triacrylate hexamethylene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate hexamethylene diisocyanate urethane prepolymer, pentaerythritol triacrylate toluene diisocyanate urethane prepolymer, dipentaerythritol pentaacrylate toluene diisocyanate urethane prepolymer, pentaerythritol triacrylate isophorone diisocyanate urethane prepolymer, and dipentaerythritol pentaacrylate isophorone diisocyanate urethane prepolymer.
[0032] The polyfunctional monomer may be used alone or in combination of two or more. The polyfunctional monomer may be a monomer in the composition or an oligomer obtained by partial polymerization.
[0033] The hydrophobic material is a component for making the hard coat layer express hydrophobicity and adjusting the moisture permeability of the protective film A. As the hydrophobic material contained in the hard coat layer, a cycloolefin polymer or a (meth)acrylate containing an alicyclic structure can be used.
[0034] As the (meth)acrylate containing an alicyclic structure, for example, (meth)acrylate having one or more of a cyclopentane structure, a dicyclopentane structure, a cyclohexane structure, a cyclodecane structure, a tricyclodecane structure, an isobornyl structure, and an adamantane structure can be used.
[0035] Specific examples of the (meth)acrylate containing an alicyclic structure include: monofunctional (meth)acrylates such as cyclohexyl (meth)acrylate, cyclohexanedimethanol mono(meth)acrylate, 4-tert-butylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexyl (meth)acrylate, 3,3,5-trimethylcyclohexanol (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, 2-dicyclopentenyloxyethyl (meth)acrylate, dicyclopentenyloxyethyl methacrylate, bornyl (meth)acrylate, isobornyl (meth)acrylate, tricyclodecyl (meth)acrylate, tricyclodecane dimethanol mono(meth)acrylate, and adamantyl (meth)acrylate; and cyclohexanedimethanol di(meth)acrylate, dicyclopentanyl di(meth)acrylate, di(meth)acrylate, and isobornyl (meth)acrylate. Polyfunctional (meth)acrylates such as dicyclopentenyl meth)acrylate, dicyclopentadienyl di(meth)acrylate, bornyl di(meth)acrylate, isobornyl di(meth)acrylate, tricyclodecyl di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, adamantyl di(meth)acrylate, adamantane dimethanol di(meth)acrylate, adamantane diethanol di(meth)acrylate, dihydroxymethyl dicyclopentane di(meth)acrylate, norbornane dimethylol di(meth)acrylate, cyclohexanedimethanol tri(meth)acrylate, adamantyl tri(meth)acrylate, adamantane trimethanol tri(meth)acrylate, norbornane trimethylol tri(meth)acrylate, tricyclodecane trimethanol tri(meth)acrylate, and perhydro-1,4,5,8-dimethylnaphthalene-2,3,7-(oxymethyl) tri(meth)acrylate. These (meth)acrylates may be used alone or as a mixture of one or more thereof.
[0036] As the photopolymerization initiator, free radical polymerization initiators such as acetophenone, benzophenone, thioxanthone, benzoin, benzoin methyl ether, and acylphosphine oxide can be used. As the polymerization initiator, for example, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide, bis (2,4,6-trimethylbenzoyl) phenyl phosphine oxide, 2,2-diethoxy acetophenone, 1-hydroxycyclohexyl phenyl ketone, 2,2-dimethoxy-phenyl acetophenone, dibenzoyl, benzoin, benzoin methyl ether, benzoin ethyl ether, p-chlorobenzophenone, p-methoxybenzophenone, Michler's ketone, acetophenone, 2-chlorothioxanthone, etc. can be used. Among these, one kind can be used alone, or two or more kinds can be used in combination.
[0037] As a solvent, any solvent that can swell or dissolve the transparent substrate can be used. One of the following solvents or a mixture of two or more thereof can be used: alcohols such as methanol, ethanol, 1-propanol, 2-propanol, butanol, isopropanol, and isobutanol; ketones such as acetone, methyl ethyl ketone, cyclohexanone, and methyl isobutyl ketone; ketone alcohols such as diacetone alcohol; aromatic hydrocarbons such as benzene, toluene, and xylene; glycols such as ethylene glycol, propylene glycol, and hexylene glycol; glycol ethers such as ethyl cellosolve, butyl cellosolve, ethyl carbitol, butyl carbitol, diethyl cellosolve, diethyl carbitol, and propylene glycol monomethyl ether; esters such as dimethyl carbonate, methyl lactate, ethyl lactate, methyl acetate, ethyl acetate, butyl acetate, and amyl acetate; ethers such as dimethyl ether and diethyl ether; N-methylpyrrolidone and dimethylformamide.
[0038] In addition, various additives such as antistatic agents, defoaming agents, antioxidants, ultraviolet absorbers, infrared absorbers, colorants, light stabilizers, inhibitors, photosensitizers, antifouling agents, leveling agents, oleophobic agents, hydrophobic agents, anti-fingerprint adhesion agents, etc. may be added to the hard coat forming composition as needed.
[0039] There is no particular limitation on the method for applying the hard coat-forming composition, and for example, coating can be performed using a spin coater, a roll coater, a reverse roll coater, a gravure coater, a micro gravure coater, an air knife coater, a rod coater, a wire bar coater, a die coater, a dip coater, a spray coater, an applicator, or the like.
[0040] The coating thickness (film thickness of the coating film) of the hard coat-forming composition is preferably set to 8 μm or less. When the coating thickness of the hard coat-forming composition exceeds 8 μm, curling is easily generated due to shrinkage during curing of the coating film, so it is not preferred. The coating thickness (film thickness of the coating film) of the hard coat-forming composition is more preferably 6 to 7 μm.
[0041] Moreover, the pencil hardness of the protective film A (hard coat film) is preferably 3 H or more. When the pencil hardness of the protective film A is 3 H or more, the surface hardness of the polarizing plate is excellent and the durability is improved.
[0042] The protective film B is a low moisture permeable film made of any one of cycloolefin polymer (COP), polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA). The protective film B is attached to the polarizer 1 via an ultraviolet curable adhesive, for example. The thickness of the protective film B is not particularly limited, but is preferably 10 to 100 μm.
[0043] In addition, in the display device, the protective film B is arranged on the display panel side, and the hard coat layer of the protective film A is arranged on the viewing side (the side opposite to the display panel).
[0044] The transparent substrate (substrate layer 2) of the protective film A is pasted on the PVA film of the polarizer 1 using a water paste (PVA aqueous solution) as an adhesive. It should be noted that in order to ensure the close adhesion between the transparent substrate and the PVA film, the protective film A is subjected to a saponification treatment before pasting. Since a water paste is used when the protective film A is pasted on the polarizer 1, moisture may be contained in the adhesive layer and the TAC film even after the drying process. In the case of using a film with low moisture permeability to constitute both the protective films A and B, although the intrusion of moisture from the outside can be suppressed, in an extremely high temperature environment such as in a car in summer, the moisture contained in the adhesive and / or the transparent substrate continues to remain in the polarizing plate 10, thereby causing the polarizer 1 to deteriorate.
[0045] Therefore, in the polarizing plate 10 involved in this embodiment, by setting a difference between the moisture permeability of the protective film A and the moisture permeability of the protective film B, and setting the moisture permeabilities of the protective film A and the protective film B within specific ranges, respectively, the deterioration of the polarizer 1 caused by moisture from the adhesive and / or TAC film is suppressed.
[0046] Specifically, when the moisture permeabilities of the protective films A and B at 40°C and 90%RH are TA and TB, respectively, TA and TB simultaneously satisfy the following conditions (1) and (2). It should be noted that both moisture permeabilities TA and TB are values measured according to the moisture permeability test method (cup method) for moisture-proof packaging materials specified in JIS Z 0208:1976.
[0047] 240g / m 2 / day>TA>70g / m 2 / day…(1)
[0048] 70g / m 2 / day≥TB…(2)
[0049] The polarizing plate 10 according to the present embodiment satisfies the above conditions (1) and (2) at the same time, thereby preventing moisture from entering the interior of the polarizing plate from the outside, and, for example, when exposed to a high temperature environment of 85°C, the moisture generated by the adhesive for attaching the protective film A to the polarizer 1 and / or the transparent substrate of the protective film A can be discharged to the outside. The moisture permeability TA is preferably 190 to 240 g / m 2 / day, more preferably 190 to 220 g / m 2 / sky.
[0050] The polarizing plate 10 is exposed to the light of the light source for a long time when assembled in the display device. Therefore, for the protective film A, it is required that the hard coating layer (the outermost layer 3) will not peel off due to degradation even when exposed to light for a long time, and the low moisture permeability and surface hardness of the protective film A can be maintained. The adhesion of the outermost layer 3 is related to the thickness of the compatible layer 4 formed on the protective film A. If the thickness is greater than a certain thickness relative to the thickness of the outermost layer 3, the adhesion between the outermost layer 3 and the substrate layer 2 is good. In addition, the thickness of the compatible layer 4 also affects the low moisture permeability of the protective film A. When the coating thickness of the hard coating forming composition is constant, the thicker the compatible layer 4 becomes, the less the thickness of the outermost layer 3 that contributes greatly to the low moisture permeability, and therefore the moisture permeability is reduced.
[0051] Specifically, the protective film A according to the present embodiment is formed so that the thickness a of the outermost layer 3 and the thickness b of the compatible layer 4 satisfy the following condition (3).
[0052] 0.60≤a / b≤0.85…(3)
[0053] When a / b is less than 0.60, the thickness of the compatibilizing layer 4 is sufficiently thick relative to the thickness of the outermost layer 3, so the adhesion of the outermost layer 3 to the substrate layer 2 is good. However, since the compatibilizing layer 4 is formed thickly, the thickness of the outermost layer 3 is insufficient, so the moisture permeability becomes high and the condition (1) cannot be satisfied. On the other hand, when a / b exceeds 0.85, since the outermost layer 3 becomes thicker, the moisture permeability becomes low, but the thickness of the compatibilizing layer 4 is insufficient relative to the thickness of the outermost layer 3, so the adhesion of the outermost layer 3 to the substrate layer 2 becomes poor. Within the range of the above condition (3), a / b is more preferably 0.61 to 0.83, and more preferably 0.69 to 0.83. The thickness a of the outermost layer 3 is preferably 2.9 to 3.6 μm, and more preferably 3.1 to 3.6 μm. The thickness b of the compatibilizing layer 4 is preferably 4.1 to 4.9 μm, and more preferably 4.1 to 4.8 μm.
[0054] As described above, the polarizing plate 10 involved in this embodiment has a protective film A and a protective film B that satisfy the above conditions (1) to (3). With this structure, the protective film B arranged on the display panel side almost blocks the entry and exit of moisture. On the other hand, the protective film A arranged on the viewing side can inhibit moisture from invading the inside of the polarizing plate 10 from the outside, and can release the moisture generated inside the polarizing plate 10 in an extremely high temperature environment. Therefore, in the polarizing plate 10 involved in this embodiment, when used in a high temperature environment, the moisture generated inside the polarizing plate 10 will not stay, so the degradation of the polarizer can be inhibited, thereby maintaining the optical performance of the polarizing plate 10 for a longer period of time.
[0055] In addition, by making the thickness of the outermost layer 3 and the compatible layer 4 of the protective film A satisfy the above condition (3), the moisture permeability of the protective film A can be suppressed, and even when irradiated with light for a long time, the degradation caused by light can be suppressed, and the adhesion of the outermost layer 3 to the substrate layer 2 can be maintained. As a result, the low moisture permeability and surface hardness of the protective film A can be maintained for a long time, and the durability of the polarizing plate can be improved.
[0056] Therefore, according to the present embodiment, it is possible to provide the polarizing plate 10 having excellent durability in a high-temperature and high-humidity environment.
[0057] The polarizing plate 10 of this embodiment can be used in combination with an image display panel such as a liquid crystal panel or an organic EL panel to form an image display device. The image display device can also have a touch panel. The polarizing plate 10 of this embodiment has excellent durability in a high temperature and high humidity environment, and can therefore be suitably used as an image display device mounted in an extremely high temperature and high humidity environment such as a car interior.
[0058] Example
[0059] Hereinafter, embodiments for implementing the present invention will be described.
[0060] A hard coat layer-forming composition was prepared containing a main material (polymerizable material), a hydrophobic material, a photopolymerization initiator, and a solvent in the proportions shown in Table 1. It should be noted that Irgacure (registered trademark) 184 shown in Table 1 is 1-hydroxycyclohexyl phenyl ketone, and TPO is diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide.
[0061] The adjusted hard coat layer-forming composition was applied onto a 40 μm thick TAC film (trade name: TJ40 manufactured by FUJI FILM) using a wire bar coater to a coating thickness as shown in Table 2. The coating was dried by heating in an oven and then cured in a UV curing device in a nitrogen atmosphere (oxygen concentration of 500 ppm or less) at a cumulative light intensity of 100 mJ / cm 2 The protective films A (hard coating films) of Examples 1 to 6 and Comparative Examples 1 to 6 were prepared by irradiating ultraviolet rays in a manner to cure the coating film. In Examples 7 and 8, a polymethyl methacrylate (PMMA) film having a thickness of 60 μm and a cycloolefin polymer (COP) film having a thickness of 26 μm were used as the protective film A. In addition, a COP film having a thickness of 26 μm was used as the protective film B.
[0062] [Table 1]
[0063]
[0064] The TAC film surface of the protective film A and the polarizer were bonded together using a water paste and dried, and then the protective film B was bonded to the polarizer using a UV curable adhesive. The UV curable adhesive was cured by irradiating with ultraviolet rays to obtain a polarizing plate.
[0065] The protective film A before being attached to the polarizer was cut in a direction perpendicular to the surface, and the cross section was photographed using a scanning electron microscope (SEM). The thickness a of the outermost layer and the thickness b of the compatibility layer were calculated based on the cross section image.
[0066] (Moisture Permeability)
[0067] According to the moisture permeability test method (cup method) for moisture-proof packaging materials specified in JIS Z 0208:1976, the moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B before being attached to the polarizer were measured under the conditions of 40°C and 90 RH%.
[0068] (Pencil hardness)
[0069] Using a pencil (uni, 3H manufactured by Mitsubishi Pencil Co., Ltd.) and a Clemens scratch tester (HA-301 manufactured by TESTERSANGYO Co., Ltd.), a scratch test was performed on the hard coat surface of the protective film A under the conditions of a load of 500 g and a scratch speed of 0.5 mm / sec. The scratch test was performed on 5 samples, and the samples with two or more scratches on the hard coat surface were evaluated as NG, and the other samples were evaluated as OK.
[0070] (Adhesion)
[0071] An ultraviolet light resistance tester (UV Fade Meter, U48, manufactured by Suga Test Instruments Co., Ltd.) was used at 40°C, 20% RH, and a radiation intensity (cumulative illuminance at 300 to 700 nm) of 500 ± 50 W / m 2 The hard coating surface of the protective film A before being attached to the polarizer was subjected to a light resistance test by irradiating light for 200 hours under the conditions of . According to the checkerboard test specified in the old JIS K 5400 general test method for coatings, 100 1 mm2 checkerboards were formed on the hard coating surface of the protective film A after the light resistance test. 2 The mesh was formed. An adhesive tape (CT405AP-24, Nichiban Co., Ltd.) was pasted on the formed mesh, and after being evenly pressed with a scraper, the adhesive tape was peeled off in a 90° direction, and the peeling of the outermost layer was visually confirmed. The peeling was judged to be present when more than 10% of the area of each mesh was peeled off, and the evaluation was OK when there were 0 peeled meshes, and NG when more than 1 peeled meshes were confirmed.
[0072] (Polarization Degree of Polarizing Plate after High-Temperature and High-Humidity Durability Test)
[0073] The polarizing plates involved in each embodiment and each comparative example were placed in a thermostatic chamber at 85°C and 85%RH, and the polarization degree was measured 240 hours and 500 hours after the placement. It should be noted that the polarization degree was calculated by correcting the value measured by an absorptiophotometer (V7100, manufactured by JASCO Corporation) with an integrating sphere using a 2-degree field of view (C light source) according to JIS Z 8701 for visibility.
[0074] Table 2 shows the properties of the protective films A and B according to the examples and comparative examples and the measured values of the polarization degree of the polarizing plate (initial value, before and after the high-temperature and high-humidity durability test).
[0075] [Table 2]
[0076]
[0077] The moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B of the polarizing plate involved in Examples 1 to 6 satisfy the above conditions (1) and (2), and the thickness a of the outermost layer and the thickness b of the compatible layer satisfy the above condition (3). Therefore, even after being placed in a constant temperature chamber at 85°C and 85%RH for 500 hours, a high value of polarization degree is shown, and the adhesion of the outermost layer after the light resistance test is excellent and the surface hardness is also good.
[0078] In contrast, in Comparative Examples 1 and 3, the value of a / b of the protective film A exceeded the range of condition (3), and the thickness of the compatibilizing layer was insufficient relative to the thickness of the outermost layer, so the adhesion of the outermost layer to the substrate layer was poor.
[0079] In Comparative Examples 2 and 4, the value of a / b of the protective film A was below the range of condition (3), and since the compatible layer became thicker and the outermost layer became thinner, the moisture permeability TA of the protective film A became higher. Therefore, the intrusion of moisture from the outside could not be sufficiently suppressed, and the polarization degree after being placed in a thermostatic chamber at 85°C and 85% RH for 500 hours deteriorated.
[0080] In Comparative Examples 5 and 6, since the hard coat layer was formed using a hard coat layer-forming composition without a hydrophobic material, the moisture permeability TA of the protective film A was high. Therefore, the intrusion of moisture from the outside could not be sufficiently suppressed, and the polarization degree after being placed in a thermostatic chamber at 85° C. and 85% RH for 500 hours was lower than that of the examples.
[0081] In Comparative Examples 7 and 8, PMMA film and COP film with extremely low moisture permeability TA were used as protective film A, respectively. However, the polarization degree deteriorated after being placed in a constant temperature bath at 85°C and 85% RH for 500 hours. It is believed that this is because the moisture permeability TA of protective film A is too low. When exposed to high temperature and high humidity, the moisture contained in protective film A and / or adhesive (water paste) continues to stay in the polarizing plate, causing the polarizer to deteriorate. In addition, since the protective film A of Comparative Examples 7 and 8 does not have a hard coating layer, the surface hardness is poor compared with the embodiment.
[0082] Industrial Applicability
[0083] The present invention can be used as a polarizing plate used in a display device, and is particularly suitable as a polarizing plate for a display device used in a high temperature environment such as in a vehicle.
[0084] Explanation of symbols
[0085] AProtective FilmA
[0086] B Protective Film
[0087] 1 Polarizer
[0088] 2. Base material layer
[0089] 3. The surface
[0090] 4 Compatibility Layer
[0091] 10 polarizing plates
Claims
1. A polarizing plate, wherein a protective film A is attached to one surface of a polarizer and a protective film B is attached to the other surface, The protective film A is a hard coating film having a hard coating layer formed on one surface of a transparent substrate, and comprises a substrate layer composed of a resin component of the transparent substrate, an outermost layer composed of a hard coating component, and a compatibility layer formed between the substrate layer and the outermost layer and containing a mixture of the resin component of the transparent substrate and the hard coating component. The moisture permeability TA of the protective film A and the moisture permeability TB of the protective film B at 40° C. and 90% RH simultaneously satisfy the following conditions (1) and (2), The thickness a of the outermost layer and the thickness b of the compatible layer satisfy the following condition (3): 240g / m 2 / day>TA>70g / m 2 / day…(1) 70g / m 2 / day≥TB…(2) 0.60≤a / b≤0.85…(3). 2 . The polarizing plate according to claim 1 , wherein the transparent substrate is a triacetyl cellulose film.
3. The polarizing plate according to claim 1, wherein the polarizing plate has a temperature of 40°C, 20% RH, and a radiation intensity of 500±50 W / m 2 After the hard coating layer of the protective film was subjected to a weathering test of irradiating light for 200 hours under the conditions of , the hard coating layer did not peel off. The polarizing plate according to claim 1 , wherein the protective film A has a pencil hardness of 3H or more. 5 . The polarizing plate according to claim 1 , wherein the protective film B is a film made of any one of cycloolefin polymer, polyethylene terephthalate, and polymethyl methacrylate. 6 . A display device comprising the polarizing plate according to claim 1 .
Citation Information
Patent Citations
Polarizing plate and display device using the same
JP2021144076A